Role of Regulatory T Cells in Tubercular Uveitis. (2nd January 2018) - Sharma, Ravi K.; Gupta, Amod; Kamal, Shivali; Bansal, Reema; Singh, Nirbhai; Sharma, Kusum; Virk, Sonia; Sachdeva, Naresh
ABSTRACT: Purpose : To study the role of regulatory T cells (Tregs) in patients with tubercular uveitis. Methods : Frequencies of peripheral Tregs, Th1, Th17 cells, and intracellular cytokines were determined in 17 tubercular uveitis patients and 18 disease controls. Function of Tregs, Th1, and Th17 cells was assessed in vitro . Simultaneously, ocular levels of IFN-γ, IL-17A, IL-4, and IL-10 were also measured. Results : Frequencies of peripheral Tregs in tubercular uveitis subjects were significantly lower compared with disease controls. Furthermore, expression of TGF-β and IL-2Rα, but not CTLA4, was reduced in Tregs of the tubercular uveitis group. The tubercular uveitis group demonstrated heightened Th1, Th17 responses following in vitro stimulation with phorbol myristate acetate (PMA)/ionomycin. Interestingly, Treg suppression assay did not show a significant difference between the two groups. Ocular levels of IFN-γ, IL-17A, and IL-10 were also elevated in tubercular uveitis group. Conclusions : Low Treg frequency and hyporesponsive function contribute to proinflammatory responses manifesting at ocular level in tubercular uveitis.